Intra-rater and Inter-rater Reliability and Agreement of the Scapular Dyskinesis test in Young Men with Forward Head and Round Shoulder Posture - Mohammad Bayattork; Foad Seidi; Hooman Minoonejad; Philip McClure; Esmaeil Mozafaripoor (Shiraz University of Medical Sciences, 2019)
Background: Forward head and round shoulder posture (FHRSP) is believed to be related to scapular dyskinesis (SD), placing increased stress on the neck and shoulder, leading to pain and dysfunction. Therefore, a clinical method with sufficient reliability to distinguish normal and abnormal scapular position and motion among people with FHRSP is called for. This study aims to evaluate intra-rater and inter-rater reliability and agreement of the scapular dyskinesis test (SDT) in people with FHRSP. MethodsːThis reliability study included 60 young men who were identified as having FHRSP, having been measured by the photogrammetry method. The clinical examination included a Scapular Dyskinesis Test (SDT), which is a dynamic and visually based test to classify the presence of SD. It was performed by two raters who were blinded to each other's test results on two different days. Intra- and inter-rater reliabilities were determined using the Kappa coefficient with linear weighting for the ordinal classification of SD by SDT. Results: Inter-rater agreement values ranged from 90.8% to 92.1%. Furthermore, the inter-rater reliabilities presented an almost perfect reliability (k > 0.82). For intra-rater agreement, raters presented high percentage values of agreement between the two measurements (88.9% to 92.5%). Intra-rater reliability for raters was substantial to almost perfect (k >0.77). Conclusion: The intra- and inter-rater reliability and agreement of the SDT obtained by two raters was substantial to almost perfect among young men with FHRSP. Therefore, it seems that SDT is a simple method to distinguish normal and abnormal scapular position and motion in order to screen or assess before developing prevention programs.